Privatisasi Ruang Publik dari Civic Centre menjadi Central Business District ( Belajar dari kasus Kawasan Simpang Lima Semarang) - Edi Purwanto (Diponegoro University, 2014)
Based on The Master Plan of Semarang City from 1975 to 2005, Simpang Lima area has been established as a Civic Centre area which its development is aimed to be a culture area broadly creating public activities for the people. During its development, due to its enormous economic potential, this area has turned into Central Business District area having several characteristics such as commercial activities, multi-storied buildings, heavy traffic, teeming street vendors and others. The impact is privatization of public space in the form of occupying of lots/buildings done by a group of businessmen owning shopping centers/hotels, using of roads for parking lot, and occupancy of pedestrian ways for street vendors. The public place privatization has prevented people to use public space freely. This problem is worthy of study. Public place privatization widely influences people because on the one hand, public place gives important meaning to people in the context of purpose, social, culture, history, and politics; on the other hand, these people will also give special meaning to this place. This study uses descriptive approach which describes and interprets the problem of public space privatization in Simpang Lima area including its impact.